Inactivation of AUF1 in Myeloid Cells Protects From Allergic Airway and Tumor Infiltration and Impairs the Adenosine-Induced Polarization of Pro-Angiogenic Macrophages - Gargani, Sofia; Lourou, Niki; Arapatzi, Christina; Tzanos, Dimitris; Saridaki, Marania; Dushku, Esmeralda; Chatzimike, Margarita; Sidiropoulos, Nikolaos D.; Andreadou, Margarita; Ntafis, Vasileios; Hatzis, Pantelis; Kostourou, Vassiliki; et al. (Frontiers in Immunology, 2022)
The four isoforms of the RNA-binding protein hnRNPD/AUF1 have been proposed to limit the use of inflammatory mRNAs in innate immune cells. Mice engineered to lack AUF1s in all tissues are sensitive to acute inflammatory assaults; however, they also manifest complex degenerations obscuring assessment of AUF1s’ roles in innate immune cells. Here, we restricted a debilitating AUF1 mutation to the mouse myeloid lineage and performed disease-oriented phenotypic analyses to assess the requirement of AUF1s in variable contexts of innate immune reactivity. Contrary to the whole-body mutants, the myeloid mutants of AUF1s did not show differences in their susceptibility to cytokine storms occurring during endotoxemia; neither in type-I cell-mediated reactions driving intestinal inflammation by chemical irritants. Instead, they were resistant to allergic airway inflammation and displayed reductions in inflammatory infiltrates and an altered T-helper balance. The ex-vivo analysis of macrophages revealed that the loss of AUF1s had a minimal effect on their proinflammatory gene expression. Moreover, AUF1s were dispensable for the classical polarization of cultured macrophages by LPS & IFNγ correlating with the unchanged response of mutant mice to systemic and intestinal inflammation. Notably, AUF1s were also dispensable for the alternative polarization of macrophages by IL4, TGFβ and IL10, known to be engaged in allergic reactions. In contrast, they were required to switch proinflammatory macrophages towards a pro-angiogenic phenotype induced by adenosine receptor signals. Congruent to this, the myeloid mutants of AUF1 displayed lower levels of vascular remodeling factors in exudates from allergen exposed lungs; were unable to support the growth and inflammatory infiltration of transplanted melanoma tumors; and failed to vascularize inert grafts unless supplemented with angiogenic factors. Mechanistically, adenosine receptor signals enhanced the association of AUF1s with the Vegfa, Il12b, and Tnf mRNAs to differentially regulate and facilitate the pro-angiogenic switch. Our data collectively demonstrates that AUF1s donot act as general anti-inflammatory factors in innate immune cells but have more specialized roles in regulons allowing specific innate immune cell transitions to support tissue infiltration and remodeling processes.